The Influence of Locus of Control Self-Efficacy and Job Satisfaction on Organizational Citizenship Behavior - Yennita, Yennita; Irawan, Hendrik; Eliza, Yulina (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia (Adpebi), 2025)
The purpose of this study is to test and analyze the influence of Locus of Control, Self Efficacy and Job Satisfaction on Organizational Citizenship Behavior atto XYX employees.The population in this study were all XYZ employees totaling 40 people. The sample in this study used saturated sampling totaling 40 people. The data collection technique in this study used observation and questionnaire techniques. Data processing in this study used the IBM SPSS Statistics 25 software program. The results of this study prove that Locus Of Control is significant to Organizational Citizenship Behavior; Self Efficacy is significant to Organizational Citizenship Behavior; Job Satisfaction is significant to Organizational Citizenship Behavior; Locus Of Control, Self Efficacy and Job Satisfaction simultaneously to Organizational Citizenship Behavior.